1982
DOI: 10.1530/acta.0.1010312
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mechanical properties, thermal stability, reducible cross-links and glycosyl-lysines in rat skin induced by corticosteroid treatment

Abstract: The effects of systemic cortisol treatment on the biophysical and biochemical properties of skin were investigated. Rats were injected sc with cortisol for 14, 60 and 120 days and samples of lumbar skin were studied. Corticosteroids exert a biphasic effect on the strength of skin: 1) a relatively fast increase in the strength and stability, caused by an increased collagen cross-linking and 2) an inhibited collagen synthesis which ultimately results in a thinning of the skin and a decrease of collagen content c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…While there is a decrease in the amount of reducible cross-links with age, there is an increase in the amount of hexitollysines, i.e., hexose attached to the &-amino group of lysine or hydroxylysine residues. It has been suggested that these hexitol-lysines may stabilize collagen (Andreassen et al 1981 ;Oxlund et al 1982). For a discussion of hexitol-lysines and of reducible cross-links see Bailey & Etherington 1980, Robins & Bailey 1973a, b, Robins et al 1973and Robins 1976 In the present study, no differences were found in the amount of hexitol-lysines or in the amount of reducible cross-links of collagen from normal corneas compared to keratoconus corneas.…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…While there is a decrease in the amount of reducible cross-links with age, there is an increase in the amount of hexitollysines, i.e., hexose attached to the &-amino group of lysine or hydroxylysine residues. It has been suggested that these hexitol-lysines may stabilize collagen (Andreassen et al 1981 ;Oxlund et al 1982). For a discussion of hexitol-lysines and of reducible cross-links see Bailey & Etherington 1980, Robins & Bailey 1973a, b, Robins et al 1973and Robins 1976 In the present study, no differences were found in the amount of hexitol-lysines or in the amount of reducible cross-links of collagen from normal corneas compared to keratoconus corneas.…”
Section: Discussionsupporting
confidence: 40%
“…The reaction was allowed to proceed for 1 h at room temperature, when acetic acid was added to a final pH of 4.0. The samples were then dialyzed against running tap water, lyophilyzed, weighed an hydrolyzed in re-distilled constant boiling 6 N HCI for 16 h. The HCI was removed by evaporation in vacuo at +40"C. The hydrolysates were then dissolved in pyridine/formate buffers, and the radioactive cross-linking components fractionated by ion exchange chromatography (Bailey et al 1970;Robins 1976;Oxlund et al 1982). Fractions were collected and the tritium activity determined in a liquid scintillation counter.…”
Section: Biochemical Methodsmentioning
confidence: 99%
“…The hydroxyproline concentration of each hydrolysate was determined as described above. From the remaining part of the hydrolysate the HC1 was removed by evaporation in vacuum, and equal amounts of the hydrolysate were submitted to ion-exchange chromatography using pyridine/formate buffers [18][19][20][21][22]. The fractions were collected and the tritium activity determined in a liquid scintillation counter.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of glucose attached to the collagen through the Eamino groups of hydroxylysine and lysine was determined by reduction of the rat tail tendon collagen with tritiated potassium borohydride as previously described [5,[18][19][20]. Tail tendons from each rat were washed extensively, immersed in phosphate buffered physiological saline and reduced by adding a solution of tritiated potassium borohydride.…”
Section: Reducible Hexosyl-lysines and Collagen Cross-linksmentioning
confidence: 99%
“…Hydroxyproline is formed intracellularly by hydroxylation of proline in the pre-pro a-chains, catalyzed by the specific enzyme proline hydroxylase, and it cannot be incorporated directly into the protein (118,(148)(149)(150). Hydroxyproline is present in the amount of 14% (w/w) in type I and 13.5% in type I11 collagen which makes quantitation of collagen in the tissues possible by measuring the amount of this amino acid (151)(152)(153).…”
Section: Hydroxyprolinementioning
confidence: 99%